Constructivist theories of political incorporation. (October 2019) - Fittante, Daniel
Drawing upon ethnographic data collected in Glendale, California, this study applies constructivist theories of ethnic politics to political incorporation research. The analysis demonstrates how the evolving loci of political incorporation—from marginalized racial minorities in urban centers to multi-ethnic migrants in prosperous suburbs—have given rise to new agents (ethnopolitical entrepreneurs) in new spaces (ethnoburbs). In these evolving spaces, community leaders emphasize, consciously and unconsciously, specific attributes, which determine, in part, whether co-ethnics support selected candidates. Specific emphases lead to both the nomination of prospective politicians as well as the political incorporation of newcomers. By applying constructivist theories of ethnic politics to the study of political incorporation, this article expands and refines discourses in both fields of study. Based upon a case study of the intra-ethnically diverse yet highly mobilized Armenian community in Glendale, California, the paper's findings synthesize the strengths of both analytical perspectives.